Reestructuración en la Ruta fluvial del Rio Magdalena, desde Neiva hasta Villavieja (Huila), con énfasis en lo económico, social y cultural (2023)
The present investigation is intended to project a fluvial connectivity, which will have the Magdalena River as its protagonist, all this will result in a connection of piers through which it will be possible to execute a portfolio focused on services such as: tourist, cultural, commercial, recreational, transportation and educational. For the consolidation of said proposal, the different contours of the region are analyzed, taking as a starting point: the infrastructure, the location, analyzing the economic, environmental, recreational, tourist impact, etc. Therefore, the need for public spaces is studied, analyzing from the point of priority that these areas should have for the growth of a sector, finally, references are defragmented, in order to increase their capacity having a base for consolidate a construction where the priority is social good.